Security measures used in Poland during football matches - Piepiora, Paweł; Sikorski, Wojciech; Supiński, Jan (Journal of Education, Health and Sport, 2019)
Football competition due to the largest number of violations of public order and order. They force the need to send significant police units to ensure their proper conduct. These violations occur both during the match and during the transport of supporters. This article presents safety issues at football matches. The hazards that may occur in a stadium during a football show are described. Security measures such as emergency exits, fire protection, CCTV monitoring, and stadium ban were presented. Controls during the match are described below: requirements for the organizer, duties of order and information services and the role of the police.